AKURASI PULSE OKSIMETRI UNTUK MENDETEKSI DILATASI VASKULAR INTRAPULMONER (DVIP) PADA PASIEN SIROSIS HATI - Sujana, I Ketut; Wibawa, I Dewa Nyoman; Santoso, Anwar (journal of internal medicine, 2012)
Hepatopulmonary syndrome (HPS) is a complication of liver cirrhotic in the lung. This clinical syndrome has three components; liver disease, intrapulmonary vascular dilatation (IPVD), and a defect in oxygenation. Transthoraxic echocardiography with contras enhancement (CE-TTE) is a gold standart method but still expensive and difficult to detect IPVD because it needs expertise. Therefore, a simple non-invasive method to detect IPVD would be desirable. In this study pulse oximetry was evaluated as predictor for identification of IPVD in patient with liver cirrhotic. Objective of ythis study is to determine the diagnostic accuracy of pulse oxymetry in detection IPVD compared with CE-TTE as a gold standart. The diagnostic test was perfomed with pulse oxyimetry in 49 consecutive patient with liver cirrhotic of >17 years old without primary cardiopulmonary diseases. Oxygen saturation (SO2) was determined using a pulse oximeter in supine and upright position. The IVPD measured by CE-TTE as gold standard. Measurement of predictor and effect variables were singgle blinded which mean the different examiner, each of them does not know the result of others. Sensitivity, specificity, positif predictive value, negative predictive value, accuracy, and likelihood ratio was calculated with computer programmed. Eight patients (16.3%) had IPVD and fourty (83.7%) without IPVD. The cut off SO2 95.5 % in supine position can predict IPVD with sensitivity 97.6% (CI 95% 72.8;100.0), specificity 87.5% (CI95% 93.2;100.0), positif predictive value 87. 0% (CI95% 78.2;96.7) negative predictive value 100% (CI95% 72.8;100.0), accuracy 95% (CI95% 75.8;100.0), positif likelihood ratio 7.8, and negatif likelhood ratio 0.3. The cut off SO2 93.0 % in upright position can predict IPVD with sensitivity 100% (CI95% 94.2;100.0), specificity 87.5% (CI95% 78.2;96.7), positif predictive value 100% (CI95% 94.2;102.2), negative predictive value 97.6 % (CI95% 93.4;100.0), accuracy 97.5%(94.1;100.0), positif likelihood ratio 8, and negatif likelhood ratio 0. The cut off slope oxygen saturation from supine to upright position ( SO2) 2.5% can predict IPVD with sensitivity 100% (CI95% 97.2;100.1), specificity 95.1% (CI95% 89.1;100.0), positif predictive value 80% (CI95% 52.0;100.0), negative predictive value 100 %, accuracy 100% (97.1;100.0), positif likelihood ratio 20.4, and negatif likelhood ratio 0. Pulse oxymetry is accurate predictor to detect of IPVD in liver cirrhotic patient without primary cardiopulmonary disease.
Keywords: Hepatopulmonary syndrome, liver cirrhotic, pulse oximetry, IPVD